Multiple directorships and earnings quality: does investor protection matter? - Abd Alhadi, Saleh; Senik, Rosmila; Johari, Jalila; Mohd Said, Ridzwana; Suhaimi Nahar, Hairul (Emerald, 2021)
Purpose – This study aims to investigate whether higher earnings quality is related to the existence of multiple directorships among corporate boards and whether his relationship varies with the quality of investor protection. Design/methodology/approach – This paper used a dynamic panel data modelling on the sample of 2,090 firm-year observations over the period from 2007 to 2016 in Malaysia. The generalized method of moments estimators were used to deal with endogeneity and other econometric problems. Findings – This study finds that the accumulation of several outside directorships is negatively associated with the firm’s earnings quality, as measured by the magnitude of discretionary accruals. More importantly, the findings provide evidence that multiple directors are more efficient in improving earnings quality in healthy investor protection environment. Practical implications – The appointment of directors should be based on market-based and not on a relationship (i.e. financial and industry professionals). Originality/value – The results highlight the importance of interaction between internal and external governance mechanisms to improve the firm’s financial performance, investment and market efficiency. High-quality investor protection and law enforcement are significant for enhancing the monitoring role of multiple directorships in improving earnings quality.